2019
DOI: 10.3892/etm.2019.7906
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of upregulated P300 expression in human cancers: A clinical study of synovial sarcoma and a meta‑analysis

Abstract: E1A binding protein p300 (P300) is a member of the histone acetyltransferase family of transcriptional co-activators, which are associated with various types of cancer. Numerous studies have evaluated the diagnostic value of P300, but their results are not consistent. Therefore, a clinical study and a meta-analysis were performed in the present study to investigate the prognostic value of P300 expression in human malignant neoplasms. Immunohistochemical (IHC) analysis was used to assess P300 expression in 43 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…It interacts with MDM2 to regulate the turnover of p53, an important tumor suppressor 22 . The prognostic value of p300 overexpression is unclear; however, it has been associated with unfavorable outcomes in patients with synovial sarcoma, and breast and laryngeal carcinomas 23 . Histologically and immunohistochemically, there were no significant differences between our case and those reported with VGLL2 ‐related fusions.…”
Section: Discussionmentioning
confidence: 57%
“…It interacts with MDM2 to regulate the turnover of p53, an important tumor suppressor 22 . The prognostic value of p300 overexpression is unclear; however, it has been associated with unfavorable outcomes in patients with synovial sarcoma, and breast and laryngeal carcinomas 23 . Histologically and immunohistochemically, there were no significant differences between our case and those reported with VGLL2 ‐related fusions.…”
Section: Discussionmentioning
confidence: 57%
“…In the paradigm of axon regeneration, it is known that many RAGs are either proto-oncogenes, or participate in signaling pathways initially discovered in tumorous cells, which may include but not limit to the abnormal expression of p300, HDACs, PTEN, and Klf family TFs found in a myriad of different types of cancers (Liu et al, 2019;Milella et al, 2015;Tetreault et al, 2013). Also, the misfunction of PI3K/Akt signaling is implicated in a variety of cancers (Janku et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…While in many cancers, the aberrant activation of the canonical WNT pathway is due to mutations in this gene or other important components of the pathway such as APC [ 21 , 112 ], in the context of STS, few CTNNB1 mutations have been described. It seems that other mechanisms such as autocrine loop activation [ 81 ], fusion proteins [ 59 , 93 , 94 ], or genomic alterations [ 60 , 63 ] have an important role in the upregulation of the WNT canonical pathway, leading to nuclear β-catenin accumulation and activation of its transcriptional program. Even so, most desmoid tumors (fibrous mesenchymal tumors, including FS) harbor somatic missense mutations in codons 41 (T41A) or 45 (S45F) of exon 3 sequence, which encodes the regulatory degradation targeting box of β-catenin.…”
Section: Deregulation Of Wnt/β-catenin Pathway In Soft Tissue Sarcomasmentioning
confidence: 99%
“…In a study of 43 SS tumor samples, Liu et al (2019) found high p300 protein expression in SS, being more prevalent in monophasic SS. Although high p300 expression has been associated with poor overall survival (OS), progression-free survival, and recurrence-free survival in various types of human cancer, such as digestive system malignant neoplasms, the prognostic value of p300 expression has not been proved yet in SS [ 94 ].…”
Section: Deregulation Of Wnt/β-catenin Pathway In Soft Tissue Sarcomasmentioning
confidence: 99%